2016
DOI: 10.1073/pnas.1608454113
|View full text |Cite
|
Sign up to set email alerts
|

Localizing gene regulation reveals a staggered wood decay mechanism for the brown rot fungus Postia placenta

Abstract: Wood-degrading brown rot fungi are essential recyclers of plant biomass in forest ecosystems. Their efficient cellulolytic systems, which have potential biotechnological applications, apparently depend on a combination of two mechanisms: lignocellulose oxidation (LOX) by reactive oxygen species (ROS) and polysaccharide hydrolysis by a limited set of glycoside hydrolases (GHs). Given that ROS are strongly oxidizing and nonselective, these two steps are likely segregated. A common hypothesis has been that brown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
214
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(258 citation statements)
references
References 58 publications
(69 reference statements)
15
214
2
3
Order By: Relevance
“…First, ˙ OH oxidation of proteins may render the proteins more susceptible to proteolytic degradation. Increased proteolysis following metal‐catalyzed radical oxidation of proteins has been demonstrated for a wide range of proteolytic enzymes and proteins (Zhang et al ., ). In the current study, aspartic protease activity was appreciably higher once BSA had been oxidized by ˙ OH (BSA growth medium) than when BSA was less oxidized (BSA–low Fe; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First, ˙ OH oxidation of proteins may render the proteins more susceptible to proteolytic degradation. Increased proteolysis following metal‐catalyzed radical oxidation of proteins has been demonstrated for a wide range of proteolytic enzymes and proteins (Zhang et al ., ). In the current study, aspartic protease activity was appreciably higher once BSA had been oxidized by ˙ OH (BSA growth medium) than when BSA was less oxidized (BSA–low Fe; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, as cell wall pores, even in the water-saturated state, are too small for enzymes to enter (Srebotnik et al 1988, Daniel et al 1989, 1990, 2004, fungi break up cell walls by oxidative action (Cragg et al 2015). While fungi classified as white-rot fungi rely on enzymes for this task (Vaaje-Kolstad et al 2010, Hori et al 2013, Riley et al 2014, another class of fungi termed brown-rot fungi have evolved a non-enzymatic strategy based on Fenton chemistry to disrupt cell walls in the initial stage of attack (Goodell et al 1997, Xu & Goodell 2001, Halliwell 2003, Arantes & Milagres 2007, Hastrup et al 2013, Schilling et al 2013, Ringman et al 2014a, Zhang et al 2016. It is speculated that through transportation of chelated iron ions into wood cell walls and reaction of these with hydrogen peroxide, brown-rot fungi create highly reactive free radicals which disrupt chemical bonds of the cell wall constituents.…”
Section: Fungal Decay Mechanisms and The Importance Of Watermentioning
confidence: 99%
“…Although P. betulinus is unable to degrade lignin, it could secrete enzymes which may modify lignin or break lignin seal by the methylation pathway and sufficiently expose cellulose and hemicellulose for enzymatic action. Recently, most of the studies were focused on Postia placenta, such as genome, transcriptome, secretome analysis and nuclear magnetic resonance analysis [27,30]. Martinez et al first reported transcriptional profile of brown-rot fungus P. placenta, and their results revealed that this fungus possessed unique extracellular enzyme systems, including an unusual repertoire of glycoside hydrolases, while exocellobiohydrolases and cellulose-binding domains were absent in this fungus [27].…”
Section: Discussionmentioning
confidence: 99%